2016
DOI: 10.17576/jkmjc-2016-3201-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Validity and Reliability of Social Media as An Empowerment Tool For A Group at Risk in Malaysia

Abstract: This article discusses a study on empowerment of a group at risk via social media in Malaysia which focuses on five important dimensions namely economy, social and cultural, legal, political, and psychology. The group at risk focused in the study refers to women. The study employed a survey that uses a set of online questionnaire distributed to women who are actively using social media, particularly social networking sites. This study involves a sample of 1,307 respondents in an exploratory study, in which a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Past studies have also found that social media can improve the level of self-confidence and resilience of women (Hamid et al, 2016) and that repeated rejection can further reduce a person's feeling of self-perceived mate value (Charlot, 2018) However, this current study further suggests that depending on the female users' point of view or personality, self-confidence can either be boosted or reduced. This finding is applicable to other mobile dating applications that also rely on the 'swiping' feature to trigger a match.…”
Section: Perceived Competencecontrasting
confidence: 61%
See 3 more Smart Citations
“…Past studies have also found that social media can improve the level of self-confidence and resilience of women (Hamid et al, 2016) and that repeated rejection can further reduce a person's feeling of self-perceived mate value (Charlot, 2018) However, this current study further suggests that depending on the female users' point of view or personality, self-confidence can either be boosted or reduced. This finding is applicable to other mobile dating applications that also rely on the 'swiping' feature to trigger a match.…”
Section: Perceived Competencecontrasting
confidence: 61%
“…Stavrositu and Sundar (2012) believe that social media platforms are gradually tapping into the Internet's claimed ability to empower. This is supported by Hamid, Ishak, and Yusof, (2016) who claim that social media plays a part in enabling women to gain control over their lives as well as improve its quality, which is in line with the definition of psychological empowerment provided by Tahir and Rana (2013). Women feel that social media can be used to improve their levels of self-confidence, resilience (Hamid et al, 2016) and gain peace of mind (Hamid et al, 2016;Stavrositu & Sundar, 2012).…”
Section: Social Media and Women Empowermentmentioning
confidence: 54%
See 2 more Smart Citations